Mathematical model building in economics and industry/ Being the collected papers of conferences organized by Scientific Control Systems Ltd and held in London in June 1968 and June 1969 and Montreal in October 1969. - Kendall, M. G.; Scientific Control Systems Ltd. (London: Charles Griffin and Company Limited, 1970)
The articles in this volume include papers given at Scicon Mode-Building Conference held in London in June 1968 & June 1969 and Montreal in October 1969. As for the first volume of papers, the objective was to organize the presentation of material by persons who had actual experience of constructing models in economics and industry, and hence would be able to discuss not only the theoretical but the practical problems involved and the experience which they had gained.
Includes bibliographical references.
rpm 01/08/2017
Loans
Keywords: Economics; Economics -- Mathematical models; Industrial management